Comparison of Modified Ferriman-Gallwey Score and Biochemical Parameters in the Estimation of the Prevalence of Idiopathic Hirsutism Among Women in the Kurdistan Region - Bushra Maree jarallah; Hataw Adil; Ayad Palani (Baghdad Journal of Biochemistry and Applied Biological Sciences)
The word "hirsutism" describes the development of terminal hairs at androgen-controlled body locations in women, which has distress and adverse psychosocial affects. The diagnosis of hirsutism is the key point in the treatment of unwanted hair growth in women’s body. Present study aimed to evaluate the modified Ferriman-Gallwey (mFG) score and the biochemical hyperandrogenism parameters among Iraqi hirsute women and their association with hirsutism in outpatients clinics in Kalar city, Garmian region, Iraq. This was a cross-sectional study of 100 hirsute women were collected from the outpatients clinic and 26 healthy women in Kalar city. After detailed history taking by using structured questionnaire, physical examination, and the relevant investigations were done, the scoring of hirsutism was indexed according to (mFG) scoring system. Moreover, sera of hormonal markers were measured; which included 17-hydroxyprogesterone (17-OHP), total testosterone (TT), free testosterone (FT), dehydroepiandrosterone (DHEA), s. prolactin, and thyroid stimulating hormone (TSH). No statistically significant differences were found in the median of the sex and related hormones between control subjects and the hirsutism group. Likewise, there were no significant relation between hormonal markers and the rate of hirsutism. While, an intrinsic statistical association was seen between the mFG score with the hirsutism and the rate of hirsutism. Our findings imply that the mFG score system is a significance screening tool and has tremendous importance and utility in establishing the diagnosis of hirsutism.